Peranan Guru Pembina OSIS dalam Membentuk Karakter Akhlakul Karimah pada Pengurus OSIS di SMPN 1 Ulakan Tapakis Kabupaten Padang Pariaman - Fauziyah Maulia; Januar Januar; Deswalantri Deswalantri; Nurhasnah Nurhasnah (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This research is based on the fact that there are still OSIS administrators at SMPN 1 Ulakan Tapakis who have not been able to reflect good morals, this is because the OSIS supervisor teachers heve not provided provisions and approaches to OSIS administrators at SMPN 1 Ulakan Tapakis and there is a lack apptoach to OSIS administrators. This research aims to describe the role of the OSIS supervisor teacher in forming the moral character of the OSIS administrators at SMPN 1 Ulakan Tapakis. The research was conducted at SMPN 1 Ulakan Tapakis, Padang Pariaman regency. This research uses descriptive research methods with a qualitative approach. The key informant in this research is the OSIS teacher, while the supporting informant is the OSIS administrator. Data collection techniques by means of beservation, interviews and documentation. The role of the OSIS supervisor teacher is very important in forming the moral character of the OSIS administrator. The role of the coaching teacher is as a guide (preceptor), providing motivation (Motivator) and providing evaluation (evaluator). Through various activities carried out by the OSIS in order to form moral character and be able to instill commendable values that exist in OSIS activites throught the form of IMTAQ development and good manners or noble morals. In order for the formation of akhlakul karimah character in OSIS administrators, it is not solely on the shoulders of religious teachers, but requires the role of the supervisor teacher as well as cooperation between the supervisor teacher and the OSIS administrators.